The Role of Digital Storytelling in Jordanian School EFL Classrooms: A Qualitative Exploration of Teachers’ Perceptions - Mohammad Hamad Al-khresheh (Theory and Practice of Second Language Acquisition)
The topic of digital storytelling in the field of EFL instruction has attracted increasing attention. However, its significance, effectiveness, and incorporation within educational settings in Jordan have not been thoroughly studied. In order to address this research gap, the present paper explores the teaching effectiveness, challenges, and practical applications of digital storytelling in Jordanian EFL classrooms, specifically through a qualitative analysis of teacher perspectives, incorporating semi-structured interviews with 26 EFL teachers recruited by purposive sampling. The thematic analysis revealed that EFL teachers in Jordan predominantly view digital storytelling as a valuable enhancement to English language teaching, notably for its ability to engage students and facilitate language learning. This positive perspective, however, is tempered by concerns over resource availability and curriculum integration challenges. The study also observed that digital storytelling positively impacts student engagement and language skills, with teachers reporting notable improvements in student involvement and language competencies. However, this impact varied among students, influenced by individual learning styles and access to technological resources. Lastly, regarding integrating digital storytelling into the curriculum, teachers identified several benefits, including the versatility of digital storytelling in achieving educational objectives and its effectiveness in facilitating interactive learning. Yet, they also faced challenges, particularly regarding inadequate technological infrastructure and difficulties aligning digital storytelling with rigid curricular structures. These findings provide crucial insights into the application of digital storytelling in EFL education in Jordan, reflecting its potential to transform teaching practices amidst practical implementation challenges. The paper concludes with limitations and future research suggestions, intending to encourage deeper scholarly and practical involvement with this novel teaching style.